Identification and Geovisualization of Landscape Transformation of Surface Mine Areas in the Đurđevik Coal Basin (Bosnia and Herzegovina) - Smajić, Sabahudin; Kovačević, Merima; Pavić, Dragoslav (Geographica Pannonica, 2021)
The paper researches the landscape transformation of the surface mines of the Đurđevik coal basin (northeastern Bosnia region), where 35.24 Mt of brown coal were produced in the past 74 years, and 227.40 Mm3 of overburden was excavated and disposed of. This type of coal exploitation caused the formation concave and convex of anthropogenic relief forms which ultimately led to significant landscape transformation. These transformations were identified and geovisualized on the basis of field research and comparative GIS analysis of archival maps, satellite images, Digital Elevation Models and plans of this area. As a result of the research, especially comparative GIS analysis of two prepared terrain models of surface mines, the transformation of hypsometry, slope and aspect, hydrographic network, pedological as well as vegetation cover were determined. Obtained geospatial data are geo-visualized in QGIS, and as a result, thematic maps were created to provide insight into the essence of transformations. Therefore, established indicators of landscape transformation can serve as a significant factor in planning the revitalization and land re-cultivation of devastated areas in the Đurđevik coal basin.